(untitled) (IUBAT Review, 2024)
The performance of public sector enterprises in Bangladesh seems to be very poor. Various combinations of factors are responsible for industries to become sick. Old machineries and technology is one of the important factors among them. Ultimately the industry gives continuous loss and it becomes sick and finally brings down the closure. This paper points out and shows how the sick industries can be improved their condition by applying application of technology. The overall objective is to overcome sickness and thus survive. IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 163-175